Effects of concurrent grain boundary and surface segregation on the final stage of sintering: the case of Lanthanum doped yttria-stabilized zirconia. Issue 3 (March 2017) - Gong, M.M.; Dey, S.; Wu, L.J.; Chang, C.H.; Li, H.; Castro, R.H.R.; Liu, F.
Abstract : Dopants play a critical role in tailoring the microstructure during sintering of compacts. These dopants may form solid solution within the bulk, and/or segregate to the grain boundaries (GBs) and the solid-vapor interfaces (free surfaces), each causing a distinct energetic scenario governing mass transports during densification and grain growth. In this work, the forces controlling the dopant distribution, in particular the possibility of concurrent segregation at both surfaces and GBs, are discussed based on the respective enthalpy of segregation. An equation is derived based on the minimum Gibbs energy of the system to determine enthalpy of segregation from experimental interface energy data, and the results applied to depict the role of La as a dopant on the interface energetics of yttria stabilized zirconia during its final stage of sintering. It is shown that La substantially decreases both GB and surface energies (differently) as sintering progresses, dynamically affecting its driving forces, and consequent grain growth and densification in this stage.